Perancangan Interior Elderly Day Care Center Sebagai Pusat Aktivitas Manula di Surabaya - Sabella Vicky P; mariana wibowo (Intra, 2014)
Modern human life in metropolitan cities of Surabaya Indonesia claimed to have high job mobility. Elderly man as one of the families who already do not have the ability to work will be home more often and be more neglected. The nursing home as a place of social services intended specifically for treating human age is not able to accommodate all the displaced seniors. This has resulted in the emergence of the idea of making an Elderly Day Care Center devoted to accomodate seniors with activities with attention to standard-satndar ekletik design and concept that is mixing between the modern and pop style to the homey ambience, fresh, and comfortable in order to support the activity of seniors in it.